Treatment of hospital wastewater by supercritical water oxidation process - Top, Selin; Akgun, Mesut; Kipcak, Ekin; Bilgili, Mehmet Sinan (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Hospital wastewater contains several micro and macro pollutants that cannot be removed efficiently by conventional treatment processes. Thus, generally hybrid and multistage treatment methods are suggested for the treatment of hospital wastewater. Supercritical water oxidation (SCWO) is a promising method for the removal of emerging organic pollutants from hospital wastewater in one step and a very short reaction time. In this study, supercritical water oxidation (SCWO) process was used for the removal of pharmaceuticals in addition to conventional pollutants from real hospital wastewater. As a result of a series of preliminary studies, the optimum conditions were selected as 450 degrees C, 60 s, and 1:1 for temperature, reaction time, and oxidant ratio (H2O2/COD), respectively, for the treatment of hospital wastewater at 25 +/- 1 MPa. The removal rates were determined above 90% for COD, BOD, TOC, TN, and SS from hospital wastewater. Phosphorus removal was greater than 90%, while the removal rates were around 80% for phenol, AOX, and surfactants in hospital wastewater. A total of 9 pharmaceuticals were observed in the real hospital wastewater samples. The highest removal rate was obtained for Paracetamol as 99.9%, while the lowest removal rate was obtained for Warfarin as 72% after SCWO treatment of hospital wastewater. As a result, it can be concluded that SCWO process is sufficient for the treatment of hospital wastewater without the need of additional treatment steps, with high removal rates in a short reaction time. (c) 2020 Elsevier Ltd. All rights reserved.
Keywords: Medical waste; Hospital wastewater; Pharmaceuticals; Supercritical water oxidation; HYDROTHERMAL TREATMENT; AQUATIC ENVIRONMENT; TREATMENT PLANTS; SEWAGE-SLUDGE; REMOVAL; OZONATION; MUNICIPAL; MICROPOLLUTANTS; DETOXIFICATION; Engineering; Environmental Sciences & Ecology; Water Resources